Effects of propofol versus sevoflurane on cerebral oxygenation and cognitive outcome in patients with impaired cerebral oxygenation - Guo JY; Fang JY; Xu SR; Wei M; Huang WQ (Dove Medical Press, 2016)
Jun-ying Guo,1,* Jie-yu Fang,1,* San-rong Xu,2 Ming Wei,1 Wen-qi Huang1 1Department of Anesthesia, the First Affiliated Hospital, Sun Yat-sen University, Guangzhou, Guangdong, 2Department of Anesthesia, Zhangzhou Municipal Hospital of Fujian Province, Zhangzhou, Fujian, People’s Republic of China *These authors contributed equally to this work Background: Postoperative neurocognitive dysfunction induced by anesthetics, particularly in elderly patients with impaired oxygenation, is a common complication of surgery and is eliciting increased interest in clinical practice. To investigate the effects of anesthetics on neurocognition, we compared the effects of propofol versus sevoflurane on cerebral oxygenation and cognitive outcome in patients with impaired cerebral oxygenation undergoing general anesthesia. Methods: Sixty-three patients with impaired cerebral oxygenation (jugular venous bulb oxygen saturation [SjvO2] <50%) or cerebral blood flow/cerebral metabolic rate of oxygen ([CBF/CMRO2] ≤15%) undergoing elective abdominal surgery were randomly allocated into propofol group (group P) or sevoflurane group (group S). The clinical parameters and jugular venous bulb blood gas analysis were monitored throughout the surgical procedure. Cognitive function was assessed with the mini-mental state examination and Montreal Cognitive Assessment at day 1 and day 7 following surgery. S100β protein in plasma was measured using enzyme-linked immunosorbent assay. Results: The SjvO2 increased during anesthesia induction and surgery when compared to baseline but had no significant difference between group P and group S. When compared to baseline, the CBF/CMRO2 was increased only at the end of surgery and extubation in group P; however, the CBF/CMRO2 in group S was increased during anesthesia induction at 1 hour, 2 hours, end of surgery, and extubation. Furthermore, the CBF/CMRO2 in group S was significantly higher than that in group P during anesthesia induction at 1 hour, 2 hours, and end of surgery. S100β protein did not significantly change at extubation and 1 day after surgery in both groups when compared to baseline. There was no significant difference in mini-mental state examination and Montreal Cognitive Assessment scores between group P and group S at all time points. Conclusion: Sevoflurane showed similar effects in postoperative neurocognitive function as propofol but could improve cerebral oxygenation in patients with impaired cerebral oxygenation. Keywords: saturation, postoperative cognitive dysfunction, propofol, sevoflurane